Effects of chronic renal failure on protein synthesis and albumin messenger ribonucleic acid in rat liver. - Zern, M A (1984)
Previously we reported that chronic renal failure in rats leads to preferential disaggregation of liver membrane-bound polysomes associated with a decrease in albumin synthesis. To determine whether reduced albumin synthesis results from reduced cellular levels of albumin messenger RNA (mRNA) or some other molecular mechanism, we have employed mRNA-DNA hybridization in conjunction with cell-free protein synthesis to determine albumin mRNA sequence content and biological activity in subcellular fractions from control and uremic rat liver. Using high specific activity albumin [3H]-complementary DNA prepared from purified-albumin mRNA, we found that total liver polysomes and albumin mRNA sequence content are increased in uremic animals. The extra polysomes are located within the membrane-bound subcellular fraction. These polysomes, however, have reduced ability to synthesize albumin in the cell-free system, and mRNA isolated from membrane-bound polysomes of uremic liver showed reduced albumin synthesis. Evaluation of albumin mRNA size by hybridization analysis revealed a reduced content of intact albumin mRNA molecules per microgram of RNA in the liver of uremic animals. This was associated with increased ribonuclease activity in uremic cytosol. The diminished albumin synthesis by membrane-bound polysomes of uremic rat liver can, therefore, be explained by enhanced degradation of albumin mRNA.